Interactive of quick response (QR) technology in learning session - Hiew, Poh Ling (2014)
Here is the briefly discussion about web based learning system using Quick Response (QR) Technology in Learning Session. With the technology will let students have opportunity interactive with QR technology in the early stage. The aim of the proposed system is to bring alternative ways for kindergarten student to learn in an easy and attractive method during their kindergarten time so that they have interest to learn and engage students actively participate with it. They can have self-learning during at home by using smartphone to scan the QR codes which can automatically link to the shortened Uniform Resource Locator (URL) generator. Besides that, when students have problem with the assessment question, they can get answer through scan the QR codes and learn from there by itself.